Entre a emancipação e a adaptação: uma análise da politica curricular para a rede estadual de ensino a partir do Documento Curricular Referencial da Bahia (DCRB) - Lima, Cléo Emidio dos Santos (2024)
This work is linked to the area of educational policy by presenting a reflection on the new curricular policy established from the Reform of the New Middle School and its BNCC. In this way, by means of documentary research, considering the modifications stated in the regulations, we seek to reflect and understand the correlation of these policies in the DCRB document and analyze its budgets for the pedagogical organization in the state network of Bahia. For documents analyzed at the national and state level, issued by the Ministry of Education, the National Council of Education, the Secretariat of Education of the State of Bahia and the State Council of Education. These are the documentary corpus of research to present the main pedagogical and operational directives and the regulatory frameworks related to the implementation of New Middle School for the state network. Part-is you basis or referential of dialectical historical materialism, an instrument capable of evidencing the contradictions, the historicity and the totality that articulates Reform as the broader social and political context. From Cunha (1977), Antunes (2015, 2018), Gramsci (1995, 2006), Fontes (2020), Mattos (2020), Corti (2019), Kuenzer (2017), Silva (2018, 2020), Silva e Souza (2022), Saviani (2020) and Malanchen e Zank (2020), constituted the main theoretical tools to reflect on the society-education relationship, as well as how the approach to curriculum policies and the disputes raised for a middle school stage. Now the DCRB has been announced a curricular proposal that provides the construction of a life project with an emancipatory basis, starting from a critical formation, it is confirmed that the clothing of the new curriculum policy formulated for the state network is in relation with the guiding principles of Reform, oriented by its pedagogical budget of pedagogy of competencies and its logic of reduction of the curriculum of public school students, being a factor in reinforcing social inequalities, of duality in education and of adaptation of subjects to the conditions imposed by neoliberalism.